2011
DOI: 10.1177/0886260511416460
|View full text |Cite
|
Sign up to set email alerts
|

Help-Seeking in a National Sample of Victimized Latino Women

Abstract: The current study aimed to examine formal and informal help-seeking responses to interpersonal victimization among a national sample of Latino women. In addition, an examination of help-seeking by victimization type was undertaken. Data came from the Sexual Assault Among Latinas (SALAS) study that obtained help-seeking rates among a victimized subsample of Latino women (n = 714; 35.7% of a national sample). Results show a majority (76.6%) of the victimized participants engaged in some form of help-seeking with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
54
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 48 publications
9
54
2
1
Order By: Relevance
“…Some authors argue that women experiencing more severe violence (involving the use of deadly objects or the fear for one's life) seek more help [91], while others, as demonstrated in our results, do not reveal any sign of the connection between the impact of severity and their help-seeking behaviour [92]. Socio-demographics (including age, education, socioeconomic, and marital status) and psychosocial health have also been shown to influence help-seeking behaviour [91,[93][94][95]. Psychosocial dysfunction associated with IPV may negatively influence a woman's help/health seeking behaviour [94].…”
Section: Help-seeking Behavioursupporting
confidence: 40%
See 1 more Smart Citation
“…Some authors argue that women experiencing more severe violence (involving the use of deadly objects or the fear for one's life) seek more help [91], while others, as demonstrated in our results, do not reveal any sign of the connection between the impact of severity and their help-seeking behaviour [92]. Socio-demographics (including age, education, socioeconomic, and marital status) and psychosocial health have also been shown to influence help-seeking behaviour [91,[93][94][95]. Psychosocial dysfunction associated with IPV may negatively influence a woman's help/health seeking behaviour [94].…”
Section: Help-seeking Behavioursupporting
confidence: 40%
“…Psychosocial dysfunction associated with IPV may negatively influence a woman's help/health seeking behaviour [94]. In contrast, psychologically healthier individuals could be more likely or better equipped to reach out for help [93]. Hence, the low psychosocial health scores at baseline might have had an impact on the effect of the intervention.…”
Section: Help-seeking Behaviourmentioning
confidence: 99%
“…For severe physical assault the number was 29% for women and 2.4% for men. This is in line with international research findings that seeking help is more common among women and among victims of severe violence (Liang, Goodman, Tummala-Narra and Weintraub, 2005;Leone, Johnson and Cohan, 2007;Schreiber, Renneberg and Maercker, 2009;Ansara and Hindin, 2010;Sabina, Cuevas and Schally, 2012). Some of the gender differences found in help-seeking after intimate partner violence have been reported to disappear when the severity of violence is accounted for (Ansara and Hindin, 2010).…”
Section: Health Care System's Response To Victims Of Violencesupporting
confidence: 89%
“…Female victims of intimate partner violence report a fear of escalating violence, shame, low self-esteem, cultural factors, obligations to family/partner, finances and a lack of knowledge about sources of help as reasons for not seeking medical help or withholding information about victimization to health care professionals (Rodriguez, Quiroga and Bauer, 1996;Hathaway, Willis and Zimmer, 2002;Liang et al, 2005;McCart, Smith and Sawyer, 2010;Sabina et al, 2012). In studies exploring what female victims of intimate partner violence want from their health care providers, a good patient-provider relationship characterized by trust, compassion, support and confidentiality is underlined.…”
Section: Health Care System's Response To Victims Of Violencementioning
confidence: 99%
“…IPV research has found that most women, some estimates as high as over 75 %, seek some sort of help (Kaukinen 2004;Sabina et al 2012). Help-seeking has been categorized as informal (comprising help from family and friends) and formal (including help from police, social service organizations, IPV support groups, shelters, counselors, and health care providers).…”
Section: Barriers To Help-seekingmentioning
confidence: 99%